Knowledge of subject area among pre-service teachers and their interest in the teaching of Arabic: a case study at Universiti Pendidikan Sultan Idris - Mamat , Arifin; Azizan, Nor Khalila (2015)
The teaching process is highlighted as a crucial issue since the main goal of teaching must be guaranteed effective. Having ready before teaching is not an exception in this regard as the teacher’s criteria in imparting knowledge to his students is expectedly intended to facilitate effective and meaningful teaching. Therefore, the study generally attempts to investigate the perceived level of pre service teachers’ readiness towards teaching arabic language in term of knowledge of subject area (ksa) and their interest in the teaching of arabic language. The study employed a survey method to gather the data. The respondents of this study were final year of pre-service teachers of bachelor degree arabic language with education at Universiti Pendidikan Sultan Idris. The study used a set of questionnaire as an instrument to collect the data. It was distributed to thirty (30) respondents and the data collected were analyzed using statistical package for social science (spss 17.0) software. The simple descriptive statistical analysis; percentage, frequency, standard deviation and mean was used to interpret the data. The findings show that the readiness in terms of ksa among pre-service teachers was at a medium level.Meanwhile, the result demonstrates a high level of interest in the teaching of arabic language among pre-service teachers. The results of findings also identified that there is no association between ksa and interest in the teaching of arabic language among population. The finding of the study recommended that pre-service teachers of the arabic language should equip themselves with the arabic language proficiency for the sake of professional development for teachers in line with the title of teacher of foreign language. At the same time the university should take serious actions towards pre-service teachers’ of the arabic language performance.